Spaces and roles of contemporary art in industrial and technological ruins - Cano Sanchiz, Juan Manuel (Arte, Individuo y Sociedad, 2022)
This article proposes some potential contributions of contemporary art to industrial and technological heritage discussions. The paper analyses the relations among art, industrial ruins, technological trash, heritage, and society from an archaeological perspective, although this standpoint is compared to and complemented with those of art and art history. First, the text presents how industrial sites and technological artefacts from the recent past are transformed for/by the artists. In doing so, it offers a preliminary basic typology of art-obsolescence relations illustrated with cases from Europe, Asia and the Americas. Four major kinds of interactions are introduced: the conversion of abandoned industrial buildings into art galleries and museums; the transformation of larger obsolete industrial/technological areas into creative hubs; the intervention of artists in industrial ruins; and the creative recycling of technological waste. Second, the text infers from the examples provided in the typology three possible functions of art regarding heritage: revelation/addition of value; mediation between the public and dark heritages; and recognition in technological and industrial history. In the end, the paper defends the role of art in the making of industrial and technological heritages, as well as in reconnecting them to society.